2012
DOI: 10.1007/s10549-012-2100-y
|View full text |Cite
|
Sign up to set email alerts
|

A randomized phase II trial of platinum salts in basal-like breast cancer patients in the neoadjuvant setting. Results from the GEICAM/2006-03, multicenter study

Abstract: Chemotherapy remains as the only systemic treatment option available for basal-like breast cancer (BC) patients. Preclinical models and several phase II studies suggested that platinum salts are active drugs in this BC subtype though there is no randomized study supporting this hypothesis. This study investigates if the addition of carboplatin to a combination of an alkylating agent together with anthracyclines and taxanes is able to increase the efficacy in the neoadjuvant treatment context. Patients with ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
105
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(109 citation statements)
references
References 29 publications
0
105
1
3
Order By: Relevance
“…The GEICAM (Grupo Español de Investigación en Cáncer de Mama) 2006-03 study of epirubicin and cyclophosphamide followed by docetaxel with or without carboplatin showed no improvement in pCR with the addition of carboplatin. 25 In the phase II GeparSixto trial, which assessed a regimen of dose-intense anthracyclineand taxane-based chemotherapy with bevacizumab with or without carboplatin, patients receiving carboplatin achieved a pCR rate of 53.2% compared with 36.9% in patients who did not. 26 In the phase II CALGB 40603 (Cancer and Leukemia Group B) study of standard anthracycline/taxane-based chemotherapy with or without carboplatin and with or without bevacizumab, the addition of carboplatin significantly increased the pCR rate (breast and axilla) in the per-protocol population by 13% (pCR with carboplatin, 54% v without, 41%).…”
Section: Discussionmentioning
confidence: 99%
“…The GEICAM (Grupo Español de Investigación en Cáncer de Mama) 2006-03 study of epirubicin and cyclophosphamide followed by docetaxel with or without carboplatin showed no improvement in pCR with the addition of carboplatin. 25 In the phase II GeparSixto trial, which assessed a regimen of dose-intense anthracyclineand taxane-based chemotherapy with bevacizumab with or without carboplatin, patients receiving carboplatin achieved a pCR rate of 53.2% compared with 36.9% in patients who did not. 26 In the phase II CALGB 40603 (Cancer and Leukemia Group B) study of standard anthracycline/taxane-based chemotherapy with or without carboplatin and with or without bevacizumab, the addition of carboplatin significantly increased the pCR rate (breast and axilla) in the per-protocol population by 13% (pCR with carboplatin, 54% v without, 41%).…”
Section: Discussionmentioning
confidence: 99%
“…, 18,19 GEICAM (Grupo Español de Investigació n del Cáncer de Mama) 2006-03, a much smaller trial (N ϭ 94), reported a nonsignificant drop in pCR (30% v 35%) when carboplatin was added to docetaxel after an anthracycline-based combination. 18 In GeparSixto (sixth German Preoperative trial), 315 patients with TNBC received wP 80 mg/m 2 , nonpegylated liposomal doxorubicin 20 mg/m 2 once per week, and bevacizumab 15 mg/kg every 3 weeks, with or without weekly carboplatin AUC 2,for 18 weeks.…”
Section: Sikov Et Almentioning
confidence: 99%
“…18 In GeparSixto (sixth German Preoperative trial), 315 patients with TNBC received wP 80 mg/m 2 , nonpegylated liposomal doxorubicin 20 mg/m 2 once per week, and bevacizumab 15 mg/kg every 3 weeks, with or without weekly carboplatin AUC 2,for 18 weeks. 19 This regimen was associated with high rates of grade Ն 3 hematologic toxicities, especially in patients assigned to carboplatin, and early treatment discontinuation because of toxicity (control arm, 36%; carboplatin arm, 49%).…”
Section: Sikov Et Almentioning
confidence: 99%
“…Four studies (18)(19)(20)(21) reported the pCR rate and five studies (18,(21)(22)(23)(24) reported the ORR in TNBC patients who were treated with a platinum-or a non-platinum-based regimen. There was significant heterogeneity between different study results (I 2 >50%, P<0.1), so the random-effects model was applied for data analysis.…”
Section: Resultsmentioning
confidence: 99%